1998
DOI: 10.1002/(sici)1097-4628(19981212)70:11<2143::aid-app7>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/polyethylene glycol-alginate microcapsules for oral delivery of hirudin

Abstract: ABSTRACT:A mild chitosan/calcium alginate microencapsulation process, as applied to encapsulation of biological macromolecules such as albumin and hirudin, was investigated. The polysaccharide chitosan was reacted with sodium alginate in the presence of calcium chloride to form microcapsules with a polyelectrolyte complex membrane. Hirudin-entrapped alginate beads were further surface coated with polyethylene glycol (PEG) via glutaraldehyde functionalities. It was observed that approximately 70% of the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 26 publications
1
67
0
1
Order By: Relevance
“…Using a solvent casting method, the self-assembled biological scaffold film was prepared using various ratios of excipients, ie, sodium alginate, polyvinyl alcohol, hyaluronic acid, xylitol, and polyethylene glycol-600, in order to attain thermosensitive properties. 29 Furthermore, the excipients used showed key pharmaceutical properties, including biocompatibility, safety, 30 anti-infective properties, controlled release, 31,32 flexibility, emollient, adhesion, spreadability, and retention ability for film formulation. [33][34][35] The physicochemical properties, drug release, and cell compatibility characteristics of the scaffold film were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Using a solvent casting method, the self-assembled biological scaffold film was prepared using various ratios of excipients, ie, sodium alginate, polyvinyl alcohol, hyaluronic acid, xylitol, and polyethylene glycol-600, in order to attain thermosensitive properties. 29 Furthermore, the excipients used showed key pharmaceutical properties, including biocompatibility, safety, 30 anti-infective properties, controlled release, 31,32 flexibility, emollient, adhesion, spreadability, and retention ability for film formulation. [33][34][35] The physicochemical properties, drug release, and cell compatibility characteristics of the scaffold film were studied.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively mild cross-linking conditions required for obtaining chitosan-coated alginate microparticles and the nontoxicity and biodegradability of these 2 naturally occurring biopolymers have enabled them to be used for the encapsulation of a wide variety of biologically active agents including proteins, [3][4][5][6][7][8][9][10][11][12][13] enzymes, [14][15][16] antibodies, 17 cells, [18][19][20][21][22][23] and DNA. [24][25][26][27] Alginate is an anionic copolymer of 1,4-linked-b -Dmannuronic acid and a -L-guluronic acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…A chitosan/PEG-alginate microencapsulation process, [25] applied to biological macro-molecules such as albumin or hirudin, was reported to be a good candidate for oral delivery of bioactive peptides. [26] Laurienzoet al [27] reported protocol for the synthesis of new alginate-g-PEG copolymers that retain the gelation characteristics of alginate. values of Na-alginate and bead diameter show the optimum yield.…”
Section: By Statistical Methodsmentioning
confidence: 99%